Evaluating Fire Performance: An Experimental Comparison of Dovetail Massive Wooden Board Elements and Cross-Laminated Timber - Hüseyin Emre Ilgın; Markku Karjalainen; Mika Alanen; Mikko Malaska (Fire, 2023)
The use of adhesives and metal connectors is vital in engineered wood product (EWP) composition. However, the utilization of adhesives poses sustainability and recyclability challenges due to the emission of toxic gases. Similarly, metal fasteners negatively impact the disposal, reusability, and recyclability of EWPs. An alternative solution that exclusively employs pure wood, known as dovetail massive wooden board elements (DMWBEs), eliminates the need for adhesives and metal fasteners. This paper presents an experimental comparative assessment of the fire/charring performance of DMWBEs and cross-laminated timber (CLT). Model-scale test specimens measuring 200 mm in thickness, 950 mm in width, and 950 mm in length were vertically tested according to EN 1363-1. The charring behavior of DMWBEs closely resembled that of solid timber, with only a slight increase in the charring rate. Charring primarily occurred in the third lamella layer out of five, with no observable flames or hot gases on the unexposed side. The dovetail detail effectively prevented char fall-off with the tested lamella thickness. CLT specimens exhibited a notable rise in the charring rate due to the fall-off of the first lamellae layer.